Long-term trends in aerosol properties derived from AERONET measurements - Z. Zhang; J. Li; H. Che; Y. Dong; O. Dubovik; T. Eck; T. Eck; P. Gupta; B. Holben; J. Kim; E. Lind; T. Saud; et al. (Atmospheric Chemistry and Physics)
Over the past 2 decades, remarkable changes in aerosol concentrations and compositions have been observed worldwide, especially over developing countries, potentially resulting in considerable changes in aerosol properties. The Aerosol Robotic Network (AERONET) offers high-precision measurements of aerosol optical parameters over about 1700 stations globally, many of which have long-term measurements for 1 or more decades. Here we use AERONET Level 2.0 quality-assured measurements to investigate long-term aerosol optical depth (AOD) and Ångström exponent (AE) trends and quality-controlled Level 1.5 inversion products to analyse trends in absorption aerosol optical depth (AAOD) and single scattering albedo (SSA) at stations with long-term records. We also classify the aerosol properties in these sites into six types and analyse the trends in each type. Results reveal decreases in AOD over the majority of the stations, except for northern India and the Arabian Peninsula, where AOD increased. AE (computed from the AOD within the range of 440–870 nm) decreased in Europe, eastern North America, and the Middle East but increased over South Asia and western North America. The decreased AE over Europe and eastern North America is likely due to decreased fine-mode anthropogenic aerosols, whereas that over the Arabian Peninsula is attributed to increased dust activity. Conversely, increased AE over northern India is probably attributed to increased anthropogenic emissions and decreased dust loading. Most stations in Europe, North America, East Asia, and South Asia exhibit negative trends in AAOD, whereas Solar_Village in the Arabian Peninsula has positive trends. SSA at most stations increases and exhibits opposite trends to AAOD but with several stations in North America and central Europe showing decreased SSA values. Trend analysis of different aerosol types further reveals the changes in different aerosol components that are related to AOD, AE, AAOD, and SSA trends. The reductions in aerosols in eastern North America mainly result from non-absorbing species. Reductions in both fine-mode absorbing species and non-absorbing aerosols are found over Europe and East Asia, but the reduction in absorbing species is stronger than that of non-absorbing species. Increased aerosols in Kanpur over northern India should be mainly comprised of fine-mode scattering species, whereas those in Solar_Village over the Arabian Peninsula are mainly dust. The majority of stations exhibit consistent monotonic trends across different seasons for these parameters.